Using crack or smoking cocaine, that is the question: the association of sociodemographic factors with self-labeling choices in France - Vuolo, Mike (Deviant behavior, 2023)
The label "crack user" is profoundly stigmatizing. Such labels are foundational to an individual’s identity, affecting how others view them, their self-perceptions, and subsequent behavior. Individuals can also resist labels such as "crack user," creating distinctions for the same behavior. To elucidate characteristics associated with self-application of stigmatizing labels, we use data from individuals (N = 50,721) serviced for smoking cocaine in French drug treatment centers (N = 263) from 2010-2020 to assess who self-labels their behavior "crack use" or does not in favor of "smoked cocaine," which are identical behaviors. Multilevel models reveal higher odds of using the less stigmatizing "smoked cocaine" in earlier years, among those with less risky cocaine use profiles, and among those not using other stimulants. Importantly, this less stigmatizing label is more common among those of high SES and outside the Paris region. An interaction demonstrates that even within Paris, those of high SES have higher odds of using this label than their lower SES Parisian counterparts. Those in privileged positions may use this alternative label to avoid stigmatization of the "crack user" label. Such distinctions potentially perpetuate inequalities associated with the more stigmatized label. We suggest that treatment centers can act as sites to combat these differences.